Synergic Anticancer Activity of Different Extracts of Ziziphusa Mauritiana and Punica Grantum L on the Inhibition of Hela Cell Proliferation and Tumor Growth in EAC Bearing Mice (Global Journal of Medical Research, 2017)
In consideration of the synthetic chemicals chemotherapy has induced obnoxious hazards, there is a ubiquitous tend towards the natural resources, which are remedially potent and affordable for the poor people. Development of phenolic compounds or extracts has become a major area medical research due to their cancer preventive effects through induction apoptosis and prevention of oxidative stress associated cancer. The present scrutiny was designed to investigate the synergic anticancer effect of Punica grantum L and Ziziphus maritiana. The ethanol extract of combination of both plants were found to be the most effective in BSL and trypan blue assay, also stimulated caspase-8 and-9 protease by fold increase in Ac-IETD-pNA. The expression of P 53 in cytoplasm and nuclei and the increase of TdT in the nuclei of carcinoma cells in mice treated while Bcl 2 expression was declined. Consequently, the synergic anticancer activity of ethanol extract of combination of both plants was proved.
Keywords: anticancer activity; apoptosis; carcinoma cells; Punica grantum L; Ziziphus maritiana